Football Performance Analysis Technology: A Bibliometric Study (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2024)
Sophisticated technology, such as the Global Positioning System (GPS), has been widely used in football. GPS is used to analyze the performance of football athletes. Few journals have discussed football performance analysis utilizing technology, with less than a hundred articles published each year. This research aimed to explore, trace, and review the development of research and publications on scientific analysis related to technology in football using bibliometric analysis. The study used the Scopus database, using the keywords ("football" OR "soccer") AND (" performance" OR "playing") AND ("technology" OR “virtual reality"). A total of 249 articles matched the specified keywords starting from 2019 and to March 2024. The study found that the highest publication occurred in 2022, with China being the top country in article publications. Meanwhile, the Institute of Electrical and Electronics Engineers Inc, NSCA National Strength and Conditioning Association, and Springer Science and Business Media Deutschland GmbH were active journals in publications.